2019
DOI: 10.1111/1460-6984.12458
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbonation on neurogenic dysphagia and an exploration of the clinical predictors of a response to carbonation

Abstract: Background The need for effective compensatory strategies in neurogenic dysphagia management has led to the exploration of sensory enhancement strategies (SES), such as carbonated liquids. Despite some positive findings, evidence related to the efficacy of carbonation as an SES is limited. Aims To determine if carbonated thin liquids reduced dysphagia symptoms and to explore clinical factors associated with response to carbonation. Methods & Procedures Participants (n = 29) with neurogenic dysphagia demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 36 publications
3
22
1
Order By: Relevance
“…Only one study to date attempted to explore factors that can predict which patients will benefit from carbonation. Turkington et al attempted to identify predictors for response to carbonation in a neurogenic dysphagia patient group and found no significant predicting factors [20]. We hypothesized that carbonation, being a SES, will be found most beneficiary in patients who have impairments in their sensory pathways.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Only one study to date attempted to explore factors that can predict which patients will benefit from carbonation. Turkington et al attempted to identify predictors for response to carbonation in a neurogenic dysphagia patient group and found no significant predicting factors [20]. We hypothesized that carbonation, being a SES, will be found most beneficiary in patients who have impairments in their sensory pathways.…”
mentioning
confidence: 89%
“…Carbonation has been explored as a SES with effects on multiple sensory pathways, including mechanical perception of the CO 2 bubbles, nociception and chemical perception of carbonic acid, a byproduct of CO 2 metabolism [12][13][14]. Its palatability has made it an easily applicable SES in the clinical setting [9,[15][16][17][18][19][20]. Studies exploring the effects of carbonation on swallowing physiology have shown conflicting results, probably due to methodological variability [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is preliminary evidence to support the use of a cold, sour and carbonated bolus to optimize swallowing. However, most research to date focuses on swallow safety and efficiency as well as temporal swallowing measures based on VFS (11)(12)(13)(14)(15). While VFS can provide some objective swallowing measures, it requires radiology and barium has been found to suppress taste intensity and palatability (16).…”
Section: Introductionmentioning
confidence: 99%
“…There is some description of limitations of secondary outcome measure in the published article (Turkington, Ward, Farrell & Wall, 2019). The VDS was used as a pragmatic framework for clinicians to agree definitions across several qualitative constructs.…”
Section: Limitationsmentioning
confidence: 99%